The effect of inositol-hexakisphosphate (phytate) on urinary risk factors for calcium oxalate urolithiasis in South African population groups with different kidney stone risk profiles : theoretical modelling, in vitro crystallisation experiments and in vivo human studies - Fakier, Saajidah (Department of Chemistry, 2016)
The principal aims of this thesis were to establish whether soluble calcium-phytate complexes inhibit calcium oxalate crystallisation and whether a higher dietary intake of phytate in South African black subjects compared to white subjects may contribute to the relative rarity of urolithiasis in this group. Potentiometric titrations were conducted to determine thermodynamic binding constants of soluble calcium-phytate complexes. Binding constants of seven complexes were identified. These were included in the data base of the Joint Experts Speciation System computer program to model the effect of phytate on the urinary supersaturation of calcium salts. Physiological concentrations of phytate failed to decrease ionized calcium and hence the urinary supersaturation of calcium salts. These theoretical predictions were then tested in an in vitro model. Calcium oxalate crystallisation experiments were conducted in simple salt solutions, artificial urine and real urine of the respective groups. The following parameters were measured: ionized calcium; calcium oxalate metastable limit; calcium oxalate particle volume-size distribution; calcium oxalate crystal nucleation, aggregation and growth kinetics. Deposited crystals were examined by scanning electron microscopy. The results confirmed those of the theoretical modelling. Furthermore, the results demonstrated that the inhibitory capacity of phytate is of a kinetic nature rather than a thermodynamic one. Phytate inhibited calcium oxalate crystal aggregation and the inhibition of calcium oxalate crystal growth was found to be independent of the physiological concentration of phytate. In vivo studies were conducted in which phytate-deficient, phytate-rich diets and a phytate supplement were administered in healthy black and white male volunteers. The baseline intake of phytate was assessed using food frequency questionnaires; urinary phytate was determined using a novel assay; biochemical and physiochemical urinary risk factors were measured. The black group had a significantly higher baseline intake of phytate culminating in a significantly higher urinary phytate excretion. No significant difference in urinary crystallisation kinetics was observed as being due to phytate per se. The findings of this thesis contribute to the pool of knowledge on urolithiasis and provide insight on the relative rarity of this disease in South Africa's black population.